Government intervention in the developed economy. - Maunder, Peter(ed) (London, 1979)
The aim of this book is to offer a collection of studies on the nature and experience of state intervention in seven developed countries. Of the seven, four are in Western Europe-France, West Germany, Sweden and the United Kingdom. The remaining three countries-Australia, Japan and the United States-are much more geographically disparate but are obvious candidates for inclusion in a text concerned with the relationship between government and industry in some of the world's leading economies. Of course other countries such as Canada, Italy and Switzerland suggest themselves for similar close examination of the influence of the state. Any dividing line is bound to be arbitrary but in defence of the present selection of countries the reader will no doubt appreciate the need for it to have been drawn tightly so as to keep the length of the book within bounds. Secondly, there was the not unimportant point that the book was not one based on a confer ence where experts on particular countries had been discussing matters of common interest. In such circumstances the greatest difficulty in writing a book with a multi-nation focus is getting a team of authors willing to be participants in an uncertain venture. That formidable task itself acted as a constraint on the geographic coverage of the volume.
Keywords: Economic Development